Supporting Menstrual Hygiene Skills in Adolescents with Autism: A Structured Learning Approach - Alfred Pakpahan; Aderson Situngkir; Siti Hilmah; Alam Khattak; Arneliza Arneliza (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
Adolescents with Autism Spectrum Disorder (ASD) often experience challenges in managing menstrual hygiene due to limitations in adaptive functioning and self-care skills. Limited preparation prior to menarche may increase dependence on caregivers and reduce independence in daily activities. This study aims to examine the effectiveness of a structured instructional approach in improving menstrual hygiene skills among adolescents with ASD within an educational context. This study employed a single-subject (A-B) design with mastery criteria and maintenance assessment. The participants were two female adolescents aged 9-10 years. The intervention targeted essential skills, including menstrual pad application, cleaning and disposal of used pads, and independent daily practice. Instruction was delivered through systematic, step-by-step procedures supported by prompting, repetition, and reinforcement to facilitate skill acquisition and retention. The results indicated that both participants achieved increased independence within 17-22 days. The acquired skills were successfully generalized and applied during naturally occurring menstruation. Parental involvement contributed to consistent practice and supported the transfer of skills across settings. These findings suggest that structured instructional strategies are effective in enhancing menstrual hygiene skills and promoting functional independence among adolescents with ASD. Integrating practical life-skill training into educational programs is essential to support puberty preparation and long-term independence.